Relevansi Kurikulum 2013 Dalam Membentuk Karakter Religius Siswa (Studi Hambatan dan Tantangan Guru PAI di Era Revolusi Industri 4.0) - Imron Rosyadi; Ainur Cahyati (PROGRESSA: Journal of Islamic Religious Instruction, 2022)
The expansion of digital and virtual systems, which is a hallmark of the fourth industrial revolution, has contributed to the loss of authority over the educational landscape. As a result, in this time and place, the religious character must be developed via education. Researchers are interested in undertaking a study named "The Relation of the 2013 Curriculum in Shaping Students' Reigius Character: Study of Barriers and Challenges of Islamic Education Teachers in the Era of Industrial Revolution 4.0" as a result of the background information provided. The researcher conducted library research using a qualitative descriptive approach for this study. This approach was used to replicate the data to support the researcher's findings. The findings of this study, which correspond to the fourth industrial revolution, have the potential to improve daily living for people. However, both the good and bad effects of this revolution were profound. To reduce the hazards brought on by the revolution, the educational sector must act quickly and appropriately. Religious character education is one of them; it seeks to encourage pupils to have excellent morals, character, and character. Both the family and the school setting, which serves as the pupils' second home, may impart this character education. In light of the 4.0 industrial revolution, it may be said that teaching pupils religious virtues are difficult for educators.